THE INTEGRATION OF MATHEMATICAL LOGIC IN SURAH AL-BAQARAH AND SURAH AN-NISA IN ACCORDANCE WITH RATIONAL NUMBERS - Fauzi, Rijal; Rizki, Ria Setiani Habbinnur; Kamila, Evi Nur; Susilawati, Wati; Ariany, Riva Lesta (Universitas Tanjungpura, 2025)
The Qur'an is a spiritual guide that contains profound logical insights and mathematical regularities that are essential for humanity to understand. However, empirically, the integration of logic and the regularity of rational numbers present in the verses of the Qur'an has not been widely acknowledged in mathematics education. This study aims to explore the integration of mathematical logic through rational numbers found in Q.S. Al-Baqarah and Q.S. An-Nisa. A descriptive method was employed, utilizing literature study research. The results indicate that verse 237 of Q.S. Al-Baqarah integrates mathematical logic with rational numbers, specifically in the context of dowry. Verses 11, 12, and 176 of Q.S. An-Nisa, which address inheritance division, also demonstrate this integration. The presence of mathematical logic related to rational numbers in the Qur'an implicitly contributes to the development of systematic thinking skills, which are essential for solving real-life problems. This integration serves as a rationale for modern mathematics education and strengthens numerical literacy and rationality among humanity.